Accuracy of the QuantiFERON-TB Gold in Tube for diagnosing tuberculosis in a young pediatric population previously vaccinated with Bacille Calmette-Guerin - Marcelo Genofre Vallada; Thelma Suely Okay; Gilda Maria B. Del Negro; Claudio Amaral Antonio; Lidia Yamamoto; Sonia Regina T. S. Ramos (Sociedade de Pediatria de São Paulo, 2014)
Objective: To evaluate the accuracy of an interferongamma release assay (QuantiFERON-TB Gold in Tube) for diagnosing Mycobacterium tuberculosis infection in a young pediatric population. Methods: 195 children previously vaccinated with BCG were evaluated, being 184 healthy individuals with no clinical or epidemiological evidence of mycobacterial infection, and 11 with Mycobacterium tuberculosis infection, according to clinical, radiological, and laboratory parameters. A blood sample was obtained from each child and processed according to the manufacturer's instructions. The assay performance was evaluated by a Receiver Operating Characteristic (ROC) curve. Results: In the group of 184 non-infected children, 130 (70.6%) were under the age of four years (mean age of 35 months). In this group, 177 children (96.2%) had negative test results, six (3.2%) had indeterminate results, and one (0.5%) had a positive result. In the group of 11 infected children, the mean age was 58.5 months, and two of them (18%) had negative results. The ROC curve had an area under the curve of 0.88 (95%CI 0.82-0.92; p<0.001), disclosing a predictive positive value of 81.8% for the test (95%CI 46.3-97.4). The assay sensitivity was 81.8% (95%CI 48.2-97.2) and the specificity was 98.8% (95%CI 96-99.8). Conclusions: In the present study, the QuantiFERON-TB Gold in Tube performance for diagnosing M. tuberculosis infection was appropriate in a young pediatric population.